Formulate and Evaluate the Herbal Syrup by Using Garlic and Ajwain Extract - Vanshita Bobde; Kavita Panday; Vinit Isankar; Minal Deolekar (Asian Journal of Pharmaceutical Research and Development, 2025)
In this study, two plants that are well-known for their therapeutic qualities in conventional medical systems—Allium sativum, or garlic, and Trachyspermum ammi, or ajwain—are used to formulate and assess a herbal syrup. The goal was to create an herbal remedy that was safe, natural, and helpful for common conditions like colds, coughs, dyspepsia, and minor infections. Allicin, which is abundant in garlic, has potent antibacterial, antioxidant, and anti-inflammatory qualities. Thymol, an ingredient in ajwain, has antifungal, antibacterial, and carminative properties.Aqueous and ethanolic extraction techniques were used to extract the active ingredients from ajwain and garlic. To increase taste and acceptability, these extracts were added to a syrup base that also contained natural sweeteners, preservatives, and flavorings. To guarantee stability and safety, the prepared syrup was further tested using a number of evaluation criteria, such as viscosity, pH, microbiological load, and organoleptic qualities (color, taste, odor, and consistency).The existence of advantageous substances such flavonoids, tannins, saponins, and phenolics was verified by phytochemical screening. When tested against common infections, the syrup’s antibacterial action was effective, especially against S. aureus and E. coli. Over the course of storage, the syrup also exhibited good microbiological and physical stability.According to the study’s findings, the herbal syrup made with ajwain, and garlic is a potential natural cure with few negative effects and a number of health advantages. It presents a viable substitute for synthetic formulations, particularly when it comes to treating respiratory and intestinal disorders. It is advised that more clinical research be done to validate its therapeutic claims and create uniform dose recommendations.